A evasão no ensino superior nos cursos de mestrado e doutorado da UFC entre os períodos de 2000 a 2023 - Silvino, Fabíola da Silva (2024)
Higher Education in Brazil has undergone profound transformations in recent years, which poses major challenges to Higher Education Institutions (HEIs). Although access to this level of education has expanded, especially with regard to enrollment, HEIs, especially private ones, have encountered increasing difficulties in attracting new students. Factors explaining this scenario include the reduction in the number of high school graduates, the commitment of family budgets to essential expenses, and broader economic and financial issues. Added to this is the challenge of offering education that meets both market demands and the expectations and language of a new generation of students. These elements may be strongly related to the increase in dropout rates. Tinto's model (1975), which analyzes the factors that can lead to student dropout beyond financial issues, as discussed in the past, will be the starting point for this analysis. Despite being a classic study, it continues to be widely cited to this day due to its valuable contributions and the improvements made by the author throughout his research. The study was developed based on secondary sources and primary data collected from the institution involved, through an electronic questionnaire. The data obtained reveal the socioeconomic profile of students in UFC's master's and doctoral programs. The research aims to verify responses to the proposed objectives, reflect on possible advances in the educational system and analyze the reasons that may lead students to drop out of courses. The analysis includes the main factors that may influence dropout, such as economic and financial difficulties, in addition to the incompatibility between academic life and the demands of the job market. After evaluating the results, it was found that the dropout process occurred due to a single reason. The study also revealed, through new constructions, elements that are more likely to lead students to drop out of studies. It is recommended that a qualitative study be carried out so that more findings can contribute to a better understanding and management of dropout in Higher Education Institutions (HEIs).